2018
DOI: 10.5194/tc-12-1273-2018
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of ice flow and mass balance for glaciers discharging into the Larsen A and B embayments, Antarctic Peninsula, 2011 to 2016

Abstract: Abstract. We analysed volume change and mass balance of outlet glaciers on the northern Antarctic Peninsula over the periods 2011 to 2013 and 2013 to 2016, using high-resolution topographic data from the bistatic interferometric radar satellite mission TanDEM-X. Complementary to the geodetic method that applies DEM differencing, we computed the net mass balance of the main outlet glaciers using the mass budget method, accounting for the difference between the surface mass balance (SMB) and the discharge of ice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 48 publications
5
71
0
Order By: Relevance
“…More recently, Chen et al [6] found that the surface elevation of the SIIS decreased at a rate of −0.07 m/year from 1992 to 2010; surface elevation was more stable after 2002 (as the LBIS retreated), and its ice area in 2015 was slightly larger than its ice area in 2009. Rott et al [29] found that the ice flow velocities for the Flask and Leppard Glaciers exhibited only modest changes after 2011 but still remained higher than velocities measured before 2002. In addition, Borstad et al [30] used assimilated observations in a constitutive framework to reproduce the evolution of the 2002 LBIS collapse and concluded that the weakening and fracturing of the ice shelf reduced its buttressing effect.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, Chen et al [6] found that the surface elevation of the SIIS decreased at a rate of −0.07 m/year from 1992 to 2010; surface elevation was more stable after 2002 (as the LBIS retreated), and its ice area in 2015 was slightly larger than its ice area in 2009. Rott et al [29] found that the ice flow velocities for the Flask and Leppard Glaciers exhibited only modest changes after 2011 but still remained higher than velocities measured before 2002. In addition, Borstad et al [30] used assimilated observations in a constitutive framework to reproduce the evolution of the 2002 LBIS collapse and concluded that the weakening and fracturing of the ice shelf reduced its buttressing effect.…”
Section: Introductionmentioning
confidence: 98%
“…Wuite et al [21] also observed several major rifts in the SIIS using advanced synthetic aperture radar (ASAR) images captured on 28 January 2004 and suggested that the 2002 collapse of the LBIS was an important factor affecting the instability of the SIIS. Flask and Leppard Glaciers exhibited moderate mass loss, while the smaller glaciers of the SIIS approached equilibrium [29]. Fast ice, also called landfast ice, is sea ice that is "fastened" to the coastline, to the sea floor along shoals, or to grounded icebergs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plying the ScanSAR technique to four sub-swaths featuring horizontal and vertical co-polarization (HH, VV, VV, HH) and look angles between 30 to 56 • . The large number of interwoven acquisitions at higher latitudes contributed to both absolute and relative accuracy as well as to reducing voids: the nine ascending and nine descending datatakes covering the Patagonian ice fields (Seal and Rogez, 2000) are listed in Table S3. The performance of SRTM, among others, was assessed by Rodriguez et al (2005), Brown et al (2005), Carabajal and Harding (2006), and Wendleder et al (2016).…”
Section: Srtmmentioning
confidence: 99%
“…While there are several studies reporting glacier mass changes of the Antarctic ice sheet (e.g. Shepherd et al 2018, Rignot et al 2019, the Antarctic Peninsula (Rott et al 2014, Rott et al 2018 and Patagonia (e.g. Malz et al 2018, less is known about the glaciers located on the sub-Antarctic islands and the potential impacts of atmospheric warming on their retreat during the 20th and 21st centuries.…”
Section: Introductionmentioning
confidence: 99%